INVESTIGATION OF DIAGNOSTIC PROCESS THROUGH THE OPINIONS OF THE FAMILIES WHO HAVE CHILDREN WITH AUTISM AND THE MEDICAL DOCTORS WHO DIAGNOSE THESE CHILDREN - (:unkn) unknown (IATED-INT ASSOC TECHNOLOGY EDUCATION A& DEVELOPMENT, 2015)
The aim of this study is to describe the current condition by interviewing the doctors who take place in the process of diagnosis in the hospitals in Istanbul and the families with children diagnosed with autism in these hospitals. The study group of this study consists of 10 families whose children were diagnosed with autism in the hospitals in 2013-2014 and 12 medical doctors who involved in the diagnosis of these children. In the process of determining the opinion of the families of children with autism and specialists for diagnosis, semi-structured interview based on the qualitative research approach was used. The findings in this study were summarized in two parts based on the opinions of the families of children who were diagnosed with autism and opinions of the specialists who served in the diagnosis of these children. When the findings of the study were considered as a whole it is seen that there are some important deficiencies such as using only screening tools such as M-CHAT, Denver, allowing 24 minutes on the average for the diagnosis, and the high cost of the supportive special education services (auditory integration, speech therapy) other than special education. The deficiencies seen during diagnosis have a negative influence on the effectiveness of the diagnostic services and also on the medical and educational services after diagnosis. Additionally, the assessment of the autistic children by only the medical examination, development (AGTE) and screening (Denver Developmental Screening Test, Modified Checklist for Autism in Toddlers [M-CHAT]) tests are considered to cause suspicions to arise in the prevalence of the autism in Turkey. Finally, specialists mentioned that problems such as: (1) the insufficiency of the duration for the diagnosis, (2) the lack of biological marker in the diagnosis, (3) the lack of following the neuro-motor development of the child, (4) insufficiency of the special education services for the autistic children provided by the state, (5) the commercialization of the foundations giving education services in autism., (6) lack of informing the families about autism, were faced during and after the diagnosis. Besides, the families mentioned that the medical diagnoses were performed in a very short time period and without observing the children in different environments and they also mentioned that the children were excluded in the educational environment and besides special education the supportive special educational services were expensive (auditory integration, speech therapy).
Keywords: Diagnosis of the Children with Autism; Opinions of the Families in the Process of Diagnosis and Opinions of the Medical Doctors